Determination of Nut Characteristics and Biochemical Components of Some Pecan Nut Cultivars - Rabia YILMAZ; Adnan Nurhan YILDIRIM; Civan ÇELİK; Yaşar KARAKURT (Yüzüncü Yıl Üniversitesi Tarim Bilimleri Dergisi)
This study was carried out to determine some fruit properties and biochemical (total oil, fatty acid composition, protein, total phenolic compounds, total antioxidant capacity, total flavonoids) characteristics of different pecan nut cultivars (Burkett, Choctaw, Mahan, Western, Wichita) grown in the Antalya Region (BATEM). It was determined that some fruit properties and biochemical contents of the cultivars used in the study. In the study, it was determined that the shelled fruit weight varied between 7.78 g (Burkett) and 11.40 g (Mahan), kernel weight between 3.45 g (Burkett) and 5.99 g (Mahan), and kernel percentage between 44.2% (Burkett) and 55.6% (Western). The total oil content of the cultivars ranged from 67.70% (Mahan) to 73.95% (Wichita), protein content from 7.45% (Mahan) to 9.76% (Western), total phenolic compounds from 115.29 mg GAE g-1 (Choctaw) to 176.65 mg GAE/g (Burkett), total antioxidant capacity from 201.36 mg TEAC g-1 (Choctaw) to 487.89 mg TEAC g-1 (Burkett), and total flavonoids from 1.84 mg Catechin g-1 (Western) to 2.24 mg Catechin/g (Mahan). In the study, oleic acid was determined as the major fatty acid, and the lowest ratio of unsaturated fatty acids was found in the Wichita cultivar (90.73%), but the highest ratio was determined in the Western cultivar (91.43%).